Simulation of airflow and aerodynamic forces acting on a rotating turbine ventilator - Farahani, Abolfazl Sousanabadi; Adam, Nor Mariah; Mohd Ariffin, Khairol Anuar (Science Publications, 2010)
Problem statement: Rotating turbine ventilators were generally found in most countries. They were simple in structure, light in weight and cheap to install. It was quite surprising that, the aerodynamics of this common device had not been numerically examined and the design process of most of these ventilators had developed progressively through trial and error methods. Approach: This study was concerned with performing simulation of airflow using CFD technique code name FLUENT so as to visualize the flow behavior around and within a rotating turbine ventilator in addition to determining the aerodynamic forces acting on this device during its operation. To achieve that, the realizable k-ε and RSM turbulence models were used by taking advantage of moving mesh method to simulate the rotation of turbine ventilator and the consequent results were obtained through the sequential process which ensured accuracy of the computations. Results: The results confirmed that, the realizable k-ε model can exhibit a reasonable performance, however not as competence as the RSM model, but of much less computation time. Conclusion/Recommendations: Results from this study, besides ensuring the reliability of utilizing the CFD method in design process of future turbine ventilators, would lead us to a conspicuous progress on increasing the efficiency at reduced cost of wind driven ventilators and similar devices.